Price, Promotion and Service Quality on The Purchase Decision of NPK Phonska Plus Fertilizer (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
Companies engaged in selling fertilizers to farmers involve various factors, including price, Promotion and service quality. Purchasing decisions at CV Semi cannot be separated from these factors. To determine whether or not each factor is present in sales, quantitative research is used at CV Semi with a survey method of respondents through a questionnaire. The results of this study indicate that price (X1) and service quality (X3) partially do not influence purchasing decisions at CV Semi. The data analysis results show that the t value generated by each independent variable is below the t table 2.034. So the alternative hypothesis (H1) is rejected, and the null hypothesis (H0) is accepted, meaning that partially there is no effect of the independent variable price (X1) and service quality (X3) on the dependent variable purchasing decisions (Y). Promotion (X3) partially affects purchasing decisions at CV Semi. From the Results of data analysis show that the t value of the independent variable is above the t table 2.034, meaning that the independent variable Promotion (X2) partially affects the dependent variable purchasing decision (Y). From the results of data analysis testing, price (X1), Promotion (X2), and service quality (X3) simultaneously influence purchasing decisions at CV Semi, where f count (24,650) > f table 2.88. Keywords: Price, Purchase Decision, Service Quality, Promotion, Fertilizer.